Novel Plant Acid Phosphatases from the Orphan Crop Lagenaria siceraria (Molina) Standl. for Phosphate Ester Synthesis - Koffi, Djary M. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2012)
Four non-specific acid phosphatases designated as BLsAP1, BLsAP2, RLsAP1 and RLsAP2 have been previously isolated from edible seeds of Lagenaria siceraria, an oleaginous cucurbit categorized as a neglected or an orphan crop. In this study, we examined the phosphotransferase activity of these biocatalysts for further biotechnological and industrial applications. Investigations revealed that each phosphatase showed ability to catalyze phosphate ester synthesis using pyrophosphate as the phosphate group donor and phenol as acceptor. To increase synthesis rates and yields of transfer product, the optimum conditions of transphosphorylation reactions were investigated. It was shown that transfer yields were highly dependent on pH, reaction period, donor and acceptor concentrations and enzyme amount. Shorter time course reactions (1.5 h at the most) were observed for optimum synthesis, suggesting energy saving for industrial processes. In experimental optimum conditions, average yields of 79.4 ± 0.5, 58.2 ± 0.6, 67.7 ± 0.5 and 62.4 ± 0.2% were obtained for reactions catalyzed by non-specific acid phosphatases BLsAP1, BLsAP2, RLsAP1 and RLsAP2, respectively. Considering these interesting phosphotransferase properties, it is likely that acid phosphatases from L. siceraria seeds would be useful to phosphorylate a wide range of nucleophile compounds. Thus, these biocatalysts could be considered as new valuable tools for bioindustrial applications.